Large spatial variation of intrahepatic HDV RNA levels without association with HBV core or S RNA levels in HDV cirrhosis patients - Rydell, Gustaf E.; Strömberg, Lucia Gonzales; Ringlander, Johan; Andersson, Maria E.; Skoglund, Catarina; Stenbäck, Joakim Bedner; Nilsson, Staffan; Castedal, Maria; Lindh, Magnus (Journal of clinical virology, 2025)
The aim of this study was to investigate correlations between levels of intrahepatic HDV RNA, HBV RNA and corresponding serum markers in patients who underwent transplantation because of HDV-induced liver disease. 10 pieces of tissue from each of five liver explants from patients that underwent transplantation because of HDV-induced liver disease were analyzed by digital droplet PCR. A large variation of the tissue levels of viral RNA was found both between and within patients. Overall, tissue levels of HBV core and S RNA were positively associated. However, no consistent association was observed between tissue levels of HDV RNA and either core or S RNA, except in one patient. Furthermore, intrahepatic HDV RNA levels did not correlate with serum HDV RNA. Instead, serum HDV RNA showed a positive correlation with serum HBsAg, a trend towards correlation with tissue HBV S RNA and a significant correlation with core RNA levels. The results suggest that intrahepatic HBsAg might be a limiting factor for HDV particle secretion, but do not support the hypothesis that HDV suppresses HBV replication. •HBV RNA and HDV RNA levels in liver tissue varied between and within patients.•Tissue levels of HDV RNA were not associated with HBV core or S RNA.•This observation does not support repression of HBV replication by HDV.•Serum HDV RNA correlated with serum HBsAg and tended to correlate with tissue S RNA.•This observation suggests that the HBsAg supply might limit HDV virion production.